The Regional Resources and Tourism Development in Developing Countries- a Case Study of Salt and Karak, Jordan - Nami Tanaka; Kazunari Tanaka; Yamaguchi Keiko; Tamagawa Eri (European Regional Science Association (ERSA), 2006)
The paper discusses the initial field surveys to understand the conditions of tourism development and its perspectives of contribution towards regional development in developing countries. The case studies of Salt and Karak cities in Jordan are focused, where some international aid projects are under implementation. It is believed some clues for sustainable tourism development for the regional development, which may be referred to other regions, can be extracted. The reasons of focusing on Jordanian cases are the increasing potential and demand of tourism development in Middle East and an accessibility of information of existing master plan and ongoing projects supported through the ODA by Japanese government. The interview survey of party concerned and field survey carried out in 2005. Both cities were established and perished in 19th century that they inherited the historical resources such as Ottoman architecture and religious ruins. However, as same as many other local cities in the world, contemporary changes in social system such as governance, transportation, economic activities, and demography forced them into decline. Therefore, they are straggling to keep their sustainability through tourism development. Yet, their tourism resources are neither popular nor equipped to attract mass tourism from all over the world such as Petra, Madaba, and Dead Sea. As the intention of the study is to focus on the impacts of tourism development in the regional development that those less advantaged and in need of revitalization areas are picked up for case studies. The study will preliminary applies the Strength, Weakness, Opportunities, and Threat (SWOT) analysis for assessing the cities. Based on the results of analysis, some positive factors of tourism development in the regional development will be discussed. The findings may includes some aspects of tourism development measures such as utilization of available tourism resources, application of renovation and re-routing of existing tourism resources in order to make use of available resources and creation of network among them, provision of technical assistance from the outside including international aid agencies and NGOs, participation and ownership building of local residents in tourism development activities, and involvement of existing training institutions in the area.
Keywords: 330